2013
DOI: 10.1186/2047-783x-18-6
|View full text |Cite
|
Sign up to set email alerts
|

Level of information about the relationship between diabetes mellitus and periodontitis - results from a nationwide diabetes information program

Abstract: BackgroundA comprehensive knowledge about the mutual influence between diabetes and periodontitis is decisive for the successful treatment of both diseases. The present investigation aimed at assessing the diabetic and periodontal conditions and, in particular, the degree of knowledge about the relationship between diabetes and periodontitis.MethodsDuring a diabetes information program, 111 nondiabetics (ND), 101 type 1 diabetics (T1D), and 236 type 2 diabetics (T2D) were subject to a medical and dental examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
3
30
0
3
Order By: Relevance
“…Chronic periodontitis (CP) is a disease caused by bacteria that destroys the periodontal connective tissue and the alveolar bone, and the damage process is thought to be a result of the complex interaction between the periodontal pathogens and the immuno‐inflammatory responses of the host 1 . Studies over the past 20 years have found that periodontitis might be related to several systemic diseases, particularly diabetes mellitus 2–4 . CP and type 2 diabetes mellitus (T2DM) could bidirectionally influence each other because of their common immuno‐inflammatory mechanisms, and patients with T2DM have a significantly higher periodontal screening index than patients with type 1 diabetes and those without diabetes 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic periodontitis (CP) is a disease caused by bacteria that destroys the periodontal connective tissue and the alveolar bone, and the damage process is thought to be a result of the complex interaction between the periodontal pathogens and the immuno‐inflammatory responses of the host 1 . Studies over the past 20 years have found that periodontitis might be related to several systemic diseases, particularly diabetes mellitus 2–4 . CP and type 2 diabetes mellitus (T2DM) could bidirectionally influence each other because of their common immuno‐inflammatory mechanisms, and patients with T2DM have a significantly higher periodontal screening index than patients with type 1 diabetes and those without diabetes 4 …”
mentioning
confidence: 99%
“…Studies over the past 20 years have found that periodontitis might be related to several systemic diseases, particularly diabetes mellitus 2–4 . CP and type 2 diabetes mellitus (T2DM) could bidirectionally influence each other because of their common immuno‐inflammatory mechanisms, and patients with T2DM have a significantly higher periodontal screening index than patients with type 1 diabetes and those without diabetes 4 …”
mentioning
confidence: 99%
“…6,7,8,9 A large number of epidemiological studies have demonstrated that T2DM may increase the risk of CP by two-to three-fold. 10,11,12 Conversely, CP may be a risk factor for worsened glycemic control in diabetic individuals and may increase the risk of related complications. 13,14 Currently, the mechanism by which T2DM influences CP is relatively clear, but the direct effect of CP on T2DM is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted by Foma et al (15) with diabetic patients found that the majority of patients had little information about diabetes, such as its causes, complications, prevention and management (15). Danquah et al (28) found that patients maintained a diet high in carbohydrates, sodium, and fat and that physical activity was generally low, and another study found that type 2 diabetes patients' awareness of oral health was inadequate (29). Dündar et al (20) reported that half of diabetic patients have adequate knowledge about diabetes.…”
Section: Discussionmentioning
confidence: 99%